Successful combination therapy with corticosteroids, biweekly intravenous pulse cyclophosphamide and cyclosporin A for acute interstitial pneumonia in patients with dermatomyositis : report of three cases - SUZUKI, Akitake; SHOJI, Norikazu; KIKUCHI, Eigo; UEKUBO, Kazuaki; AOKI, Naoko; SONODA, Yui; TORIGAI, Hideyuki; YAMASHITA, Hiroyuki; FUJITA, Kentaro; OKAI, Takahiro (Japanese Journal of Clinical Immunology, 2013)
We report three patients with dermatomyositis (DM) complicated with acute interstitial pneumonia (AIP). All of them complained of fever and acutely worsening dyspnea and were treated immediately by combination therapies with pulse therapy with methylprednisone (mPSL) followed by corticosteroids, biweekly intravenous pulse cyclophosphamide (IVCY) and cyclosporine A (CSA). They recovered rapidly soon after an initiation of this combination regimen. Early intervention with aggressive combination therapy is life-saving for the treatment of AIP in patients with DM.